ВЗАИМОСВЯЗЬ ЭЛЕКТРИЧЕСКОГО ПОЛЯ ПОГРАНИЧНОГО СЛОЯ АТМОСФЕРЫ С ЛУННЫМИ И СОЛНЕЧНЫМИ ПРИЛИВАМИ - Грунская, Л. В.; Исакевич, В. В.; Ефимов, В. В.; Закиров, А. А.; Рубай, Д. В. (Одеські астрономічні публікації, 2011)
The work is connected with experimental study of predicted theoretical possible interconnection of electromagnetic fields with gravitational tide influence (in particular moon gravitational tides) [1]. The object of the investigations is electromagnetic field in the Earth – ionosphere resonator.Our world is non-linear. Attempts to analyze complex processes in which a lot of objects of the classical spectral analysis showed its insuffiency. Detection of influence on tide processes on the Earth electromagnetism require great time series (continuous registrations for a year) and they are not stationary time processes. Using classical spectral analysis in such situation firstly isn’t legal and secondly, as it turned out, doesn’t allow to detect for sure the influence of the gravitational moon tides on the electromagnetic fields. There was used a method of the analysis of the latent vectors of the time series covariance matrix for exposing influence of the moon tides on Ez. The method allows to distribute an experimental signal into non-correlated periodicities. The present method is effective just in the situation when energetical deposit because of possible influence of moon tides upon the electromagnetic fields is little.